Morphometrical analysis of the p53 tissue marker in prostatic adenocarcinoma and its relationship to Gleason score and PSA level: Morfometrična analiza tkivnega označevalca p53 v adenokarcinomu prostate v povezavi z oceno po Gleasonu in vrednostjo PSA - Munda, Miha; Dariš, Barbara; Hajdinjak, Tine; Kavalar, Rajko; Štiblar Martinčič, Draga (Acta Medico-Biotechnica, 2021)
Purpose: Prostate cancer is one of the most common malignancies worldwide. The possible prognostic value of tissue markers, such as p53, may give a better understanding of this disease, improve staging accuracy, and help in choosing optimal treatment. In this study, we examined p53 expression and its correlation with Gleason score, prostate–specific antigen (PSA) levels, and patient age in a Slovenian population.Methods: This retrospective pilot study included 25 radical prostatectomy patients. The immunohistochemical expression of p53 was determined and expressed as a p53 index. In addition, correlations between p53 index, Gleason score before and after prostatectomy, PSA level, and patient age were statistically evaluated.Results: The p53 tissue marker was unevenly distributed in prostate cancer independently of local Gleason pattern; however, its expression correlated with Gleason score after prostatectomy and showed borderline correlation with PSA. There were also statistically significant correlations between Gleason score before and after prostatectomy, PSA level, and patient age.Conclusions: Despite the low number of cases presented in this study, our results demonstrate that p53 may have predictive value in prostate cancer. Thus, p53 is a promising tissue marker that can be used as an additional diagnostic parameter.
Keywords: prostate cancer; tissue markers; p53; immunohistochemistry